Aaron Temkin BECK: After Cricitical Thinking to A Creative Psychotherapy Theory - Mehmet DİNÇ (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
There is growing interest in the cognitive psychotherapy all around the world including Turkey. According to American Institute of Cognitive Therapy; cognitive psychotherapy is the fastest growing and most rigorously studied kind of talk therapy and it is practiced around the world, taking hold in places from the Middle East to Japan. Cognitive psychotherapy was designed first by Aaron Temkin Beck in 1950’s. He has published over 450 articles and authored or co-authored seventeen books and he has been listed as one of the “10 individuals who shaped the face of American Psychiatry” and one of the 5 most influential psychotherapists of all time since then. Beck’s groundbreaking systematic research established for the first time the efficacy of any psychotherapy for the treatment of depression. Moreover he not only developed and tested an effective short-term treatment (cognitive therapy) for depression, but he and his former students have successfully adapted cognitive therapy to a wide range of other psychiatric disorders as well. Numerous controlled clinical trials have now demonstrated that cognitive therapy is effective in a variety of psychiatric conditions including depression, bulimia nervosa, hypochondriasis, social phobia, obsessive-compulsive disorder, substance abuse, body dysmorphic disorder, and post-traumatic stress disorder. Therefore knowing the father of cognitive therapy and his journey from 1950’s to 2010’s will help to understand cognitive therapy and its development during these years. This article aims to give an overview of the historical background to contemporary cognitive and cognitive-behavioral approaches to psychotherapy by focusing on Beck’s life, characteristics and works.